Implementasi Metode Analytical Hierarchy Process Dalam Menentukan Kelayakan Guru Penerima Umrah - Hasan, Yasir (LPPM UNIKA Santo Thomas Medan, 2018)
Umrah means carrying out tawaf in the Ka'bah and sa'i between Shofa and Marwah, after using the ihram taken from the miqat. It is often referred to as the small Umrah pilgrimage for teachers every year who have loyalty and other best criteria. The number of hikmatul fadillah foundation teachers often makes the team of selectors confused in determining the best teacher to be given Umrah, because each of the teachers has criteria. Analytical Hierarchy Process (AHP) is a decision support model that will describe multi-factor problems or complex multi criteria into a hierarchy. With hierarchy, a complex problem can be broken down into groups which are then arranged into a hierarchical form so that the problem will appear. more structured and systematic